The State of the Art: Application of Green Technology in Sustainable Pavement. (3rd June 2018) - Sun, Wenjuan; Lu, Guoyang; Ye, Cheng; Chen, Shiwu; Hou, Yue; Wang, Dawei; Wang, Linbing; Oeser, Markus
Abstract : A wide range of literature on predominant green technologies for sustainable pavements is summarized in this paper. It covers two major aspects: energy harvesting technologies and permeable pavement systems. Fundamental mechanics of energy harvesting techniques and possible designs of energy harvesters are described, with the evaluation of energy conversion efficiency, and advantages and disadvantages. In addition, the designs of permeable pavement systems are discussed, along with their advantages and disadvantages. The latest technical innovations are highlighted. It is found that green technologies are promising for developing more sustainable pavements. Application issues are also pointed out, including construction challenges, durability, and life-cycle cost-benefit assessment. Future research directions are suggested to address practical challenges, such as efficient design, construction challenge, timely maintenance, and life-cycle performance assessment.